Returns to Education: The Causal Effects of Education on Earnings, Health and Smoking - James J. Heckman; John Eric Humphries; Gregory Veramendi (Institute for the Study of Labor (IZA), 2016)
This paper estimates returns to education using a dynamic model of educational choice that synthesizes approaches in the structural dynamic discrete choice literature with approaches used in the reduced form treatment effect literature. It is an empirically robust middle ground between the two approaches which estimates economically interpretable and policy-relevant dynamic treatment effects that account for heterogeneity in cognitive and non-cognitive skills and the continuation values of educational choices. Graduating college is not a wise choice for all. Ability bias is a major component of observed educational differentials. For some, there are substantial causal effects of education at all stages of schooling.
Keywords: C32; C38; I12; I14; I21; 330; education; earnings; health; rates of return; causal effects of education; cognitive skills; non-cognitive skills